Influence of the porphyrin structure and linker length on the interfacial behavior of phospholipid-porphyrin conjugates - Bronstein, Louis-Gabriel; Cressey, Paul; Abuillan, Wasim; Konovalov, Oleg; Jankowski, Maciej; Rosilio, Véronique; Makky, Ali (Journal of colloid and interface science, 2022)
Hypothesis - Phospholipid-porphyrin (Pl-Por) conjugates consist of porphyrin derivatives grafted to a lysophosphatidylcholine backbone. Owing to their structural similarities with phospholipids, Pl-Por conjugates can self-assemble into liposome-like assemblies. However, there is a significant lack of information concerning the impact of the porphyrin type and the length of the alkyl chain bearing the porphyrin on the interfacial behavior of the Pl-Por conjugates. We hypothesized that changing the chain length and the porphyrin type could impact their two-dimensional phase behavior and modulate the alignment between the two chains. - Experiments - 6 Pl-Por conjugates with different alkyl chain lengths in the sn2 position of C16 lysophosphatidylcholine and coupled to either pheophorbide-a or pyropheophorbide-a were synthesized. Their interfacial behavior at the air/water interface was assessed using Langmuir balance combined to a variety of other physical techniques including Brewster angle microscopy, atomic force microscopy and X-ray reflectometry. - Findings - Our results showed that all 6 Pl-Por form stable monolayers with the porphyrin moiety at the air/water interface. We also showed that changing the porphyrin moiety controlled the packing of the monolayer and thus the formation of organized domains. The chain length dictated the structure of the formed domains with no evidence of the alignment between the two chains.